Role of Regenerating Islet-Derived Protein 3A in Gastrointestinal Cancer - Zhang, Meng-ya; Wang, Jun; Guo, Jie (Frontiers in Oncology, 2019)
Regenerating islet-derived protein3A(Reg3A), a protein specifically expressed in the digestive tract, has been found over-expressed in many kinds of gastrointestinal cancer, including hepatocellular carcinoma, pancreatic cancer, gastric cancer and colorectal cancer, therefore has been considered as a promising tumor marker. In recent years, considerable attention has been focused on the tumorigenesis effects of Reg3A, which were mainly manifested as cell proliferation promotion, cell apoptosis inhibition, the regulation of cancer cell migration and invasion. In particular, based on the significant up-regulation of Reg3A during pancreatic inflammation as well as its tumorigenic potential, Reg3A has been considered to play a key role in inflammation-linked pancreatic carcinogenesis. In addition, we here systematically generalized the reported Reg3A-related signaling molecules, which included JAK2-STAT3- NF-κB, SOCS3, EXTL3-PI3K-Akt, GSK3β, Wnt/β-catenin as well as some invasion and migration-related genes (Snail, MMP-2, MMP-9, E-cadherin, RhoC and MTA1). And gp130, EGFR, EXTL3 and Fibronectin 1 might act as potential receptors for Reg3A.